Kinerja Kepala Sekolah: Pengaruh Kepemimpinan Transformasional, Konflik dan Efikasi Diri - Rosmala Dewi (Jurnal Ilmu Pendidikan, 2013)
Abstract: Effects of Transformational Leadership , Conflict, and Self-Efficacy on Principals’ Perormances.  The explanatory study was aimed at describing the effects of transformational leadership, conflict, and self-efficacy on principals’ performances. From the population of all the principals of elementary schools in Medan (380 people), a sample of 200 principals were randomly selected. The data were col lected using a questionnaire and then analyzed statistically using path analyses. The results showed that transfo rmational leadership, conflict, and self-efficacy directly influence the performance of principals, and that there are indirect effects of transformational leadership  on performance through self-efficacy and conflict.